Diogenes’ syndrome - Maliszewska, Adrianna; Banaszczyk, Katarzyna; Owsiany, Michał; Maliszewska, Patrycja (Journal of Education, Health and Sport, 2018)
Diogenes’ syndrome is a severe, life-threatening neurobehavioral disorder. Its main symptoms are complete negligence of ones hygiene, domestic squalor, emotional and social detachment as well as pathological hoarding of unnecessary things (mostly rubbish). In most cases, it affects elderly and lonesome people. This article shows the history of said disease, starting from early mentions, then going through researches conducted by Duncan Macmillan and Patricia Shaw in 1966, up until later studies done by Clark and his colleagues - this team labeled said illness in 1975 as Diogenes’ syndrome. What is more, their work covered majority of the most frequent indications along with its questionable etiopathogenesis. In addition, this article contains criteria, presented by Shehryar Khan in The American Journal of Psychiatry Residents' Journal, that can help in diagnosing this affliction. The fact that there is still very little knowledge about the therapy nor the diagnosis of Diogenes’ syndrome makes it difficult to treat. This paper describes the newest reports concerning epidemiology and the effectiveness of pharmacological treatment. The aim of that article is to gather and summarize up-to-date knowledge about said disease. Our main concern is the current, very low acquaintance with Diogenes’ syndrome which brings the challenge to the current state of medicine, especially psychiatry.